Implementasi Undang-Undang Kesehatan Jiwa Dalam Menjamin Perlindungan Masyarakat Dengan Gangguan Kejiwaan - Naurah, Gladdays; Simarmata, Marice (Cattleya Darmaya Fortuna, 2024)
Mental health is a crucial component of public health that is often neglected. According to data from the Ministry of Health of Indonesia, around 20% of Indonesia's population experiences mental health disorders. The Indonesian government has enacted Law No. 17 of 2023 on Mental Health to provide legal protection for individuals with mental health disorders; however, its implementation still faces challenges, including social stigma and limited public awareness. This study aims to analyze the implementation of the Mental Health Law, identify challenges in its execution, and evaluate the effectiveness of mental health services following the law's enactment. The study findings indicate that successful implementation requires collaboration between the government, healthcare providers, and society, as well as stringent oversight of mental health services. Through a comprehensive approach, mental health services in Indonesia are expected to improve, reducing stigma and discrimination against individuals with mental health disorders.